Diagnostic Approach and Management of Clostridium difficile Infection - Hosea, Fransiscus Nikodemus; Fauzi, Achmad (The Indonesian Society for Digestive Endoscopy, 2023)
Clostridium difficile infection (CDI) was first viewed as a nosocomial infection as it is associated with antibiotics administration. But since antibiotics are more frequently to be prescribed in the community setting, clinicians should investigate the probability of all antibiotics-associated diarrhea as CDI.Diagnostic of CDI should be conducted cautiously as the manifestation of CDI varies from asymptomatic to fatal consequences and is associated with morbidity, mortality, recurrence risk, outbreak possibility, and low quality of life. Management of this infection should include infection prevention and control, stopping the offending antibiotics, and administration of specific antimicrobials.Clinicians should also recognize the risk of recurrence and the higher probability of less efficacious specific antimicrobials in each episode of recurrence.